2014
DOI: 10.1038/gim.2014.50
|View full text |Cite
|
Sign up to set email alerts
|

Public preferences for the return of research results in genetic research: a conjoint analysis

Abstract: Purpose Recent policies specifying criteria about which individual research results (IRRs) to return leave considerable discretion to researchers. This study investigated which types of results the public wants when participating in genetic research and whether preferences differ based on willingness to participate. Methods A representative survey of U.S. adults used conjoint analysis to measure priorities among eight principles of a results policy for a proposed large-cohort study. Policy preferences were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 36 publications
5
47
0
Order By: Relevance
“…Although 7% (n = 35) of the relatives and controls reported having had a cancer during the interval between baseline (1998) and this survey (2013), cancer status at the last follow-up was not significant in any of the scenarios (results not shown) and is unlikely to account for the lack of differences between these 3 groups. Further, our findings are similar to other studies showing that research participants favor the return of individual results [17][18][19][20][21]. Nevertheless, in the light of the borderline statistical significance for the casecontrol comparison in scenarios 2 and 3, we cannot exclude that lack of statistical power limited our ability to find case-control differences.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Although 7% (n = 35) of the relatives and controls reported having had a cancer during the interval between baseline (1998) and this survey (2013), cancer status at the last follow-up was not significant in any of the scenarios (results not shown) and is unlikely to account for the lack of differences between these 3 groups. Further, our findings are similar to other studies showing that research participants favor the return of individual results [17][18][19][20][21]. Nevertheless, in the light of the borderline statistical significance for the casecontrol comparison in scenarios 2 and 3, we cannot exclude that lack of statistical power limited our ability to find case-control differences.…”
Section: Discussionsupporting
confidence: 76%
“…Most groups involved in genetic research agree that individual genetic findings that are highly penetrant (highly related to outcomes) and clinically actionable (useful in clinical practice) should be returned to the participant [17][18][19][20][21][22][23][24], although several studies have found that many researchers do not return results even if they be- lieve that they should [25][26][27]. The most commonly cited reasons for not returning individual research results were expecting participants would have difficulty understanding the results, trouble contacting participants, or not considering the option [27].…”
Section: Discussionmentioning
confidence: 99%
“…Such an endeavour will require research into the best way to communicate the range of possible inci dental findings. 23 In relation to the statement of the American College of Medical Genetics and Genomics working group, 5 we found support for returning 30 However, that study did not examine willingness to pay or uptake of scen arios related to the statement of the working group. 5 Furthermore, it did not explicitly examine tradeoffs for returning results that did and did not have medical treatment available.…”
Section: Discussionmentioning
confidence: 66%
“…that the majority of participants would welcome the opportunity to receive at least some results as a tangible benefit of participation, particularly if the results were validated and clinically actionable (Murphy-Bollinger et al, 2014;Siminoff et al, 2016). In fact, 40% of participants erroneously believed that they would receive information about their loved one's health from the GTEx project (Siminoff et al, 2016).…”
Section: Discussionmentioning
confidence: 99%